NIMH project accept (HPTN 043) HIV/AIDS community mobilization (CM) to promote mobile HIV voluntary counseling and testing (MVCT) in rural communities in northern thailand: Modifications by experience - Kawichai,S. (Springer New York, 2015)
Project Accept is a RCT designed to test the efficacy of community mobilization (CM), mobile voluntary counseling and testing (MVCT), and post-test support services (PTSS) in reducing HIV incidence in three African countries and Thailand. The intervention started in rural areas, northern Thailand in January 2006. CM initially included door-to-door visits during the daytime, small group discussions and joining organized meetings and followed by MVCT. In February 2007, CM strategy using HIV/AIDS "edutainment" (education and entertainment) during evening hours was introduced. After edutainment was initiated, the number of participants increased substantially. VCT uptake increased from 18 to 28 persons/day on average (t test; t = 7.87 P\0.0001). Edutainment especially motivated younger people, as the median age of VCT clients decreased from 38 to 35 years old (median test; z = 6.74, P\0.0001). Providing free MVCT in community settings along with edutainment during evening hours increased VCT uptake and was particularly attractive to younger adults. © Springer Science+Business Media, LLC 2011.